4-Methyl-N-[(5-nitrothiophen-2-yl)methylidene]aniline - Cai, Mingjian (International Union of Crystallography, 2011)
The title compound, C(12)H(10)N(2)O(2)S, is a Schiff base formed from p-toluidine and 5-nitrothiophene-2-carbaldehyde. The C=N bond adopts an E configuration. The benzene and thiophene rings form a dihedral angle of 9.2 (1)°.